Stability and Synchronization of a Fractional-Order Unified System with Complex Variables - Yanyun Xie; Wenliang Cai; Jing Wang (Discrete Dynamics in Nature and Society)
In this paper, a fractional-order unified system with complex variables is proposed. Firstly, the basic properties of the system including the equilibrium points and symmetry are analyzed. Bifurcations of the system in commensurate-order and incommensurate-order cases are studied. Tangent and period-doubling bifurcations can be observed when a derivative order or a parameter is varied. The stabilization the system is investigated via the predict feedback method. Based on the stability theory of fractional-order systems, a projective synchronization for the fractional-order unified complex system is proposed by designing an appropriate controller. Numerical simulations are applied to verify the effectiveness of the proposed scheme.